The Phenomenon of Teenage Abortion. - Espedilla, Naomi A.; Lanugan, Ruthsen B. (Tacloban City Naomi A. Espedilla, 2011)
The study basically aims to analyze and understand the phenomenon of teenage abortion. It mainly sought to discover factors that influence teens in doing abortion as well as the major causes and reasons for their action. Moreover the researchers dwell on the methods used and the possible effects of abortion such as number of physical, psychological, emotional, sexual and social problems. Furthermore, the process of healing and recovery of teens is also the objective of the study.
The respondents of the study were fifteen (15) women ages 20-25 years old who experienced abortion during their teenage years (13-19) years old. The study was conducted in Tacloban City for the convenient purposes of the researchers. The researchers used the qualitative method of research in gathering the data needed, in which they conducted an interview using an interview schedule and purposive sampling as technique in research procedure.
The study showed that changes in the body were the most physiological effect of it. Psychologically, it causes one to experience flashbacks, sleep anxiety, envy towards other children and alcohol intake. On emotional aspect, most of the effects were depression, anger and inability to express emotions. Moreover, most of the respondents broke up with their partners after the abortion. The strategies used in coping these effects were social support from friends, partner and being focused in studies. The study concluded that abortion happens because of fear, and the common method used was medicine specifically cytotic which gives a lot of negative effects in women's life where their parents or families are not part of coping with it.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science